Respiratory rate–oxygenation index and National Early Warning Score 2 score are associated with orotracheal intubation in patients with cardiogenic pulmonary oedema - Souza, Isabelle de Almeida [UNESP]; Shalova, Asiya [UNESP]; Vieira, Nayane Maria [UNESP]; Barros, João Carlos Clark [UNESP]; Ferreira, Gustavo Martins [UNESP]; Azevedo, Paula Schmidt [UNESP]; Polegato, Bertha Furlan [UNESP]; Zornoff, Leonardo Antônio Mamede [UNESP]; Paiva, Sérgio Alberto Rupp de [UNESP]; Lazzarin, Taline [UNESP]; Minicucci, Marcos Ferreira [UNESP] (Elsevier, 2025)
Background: This study evaluates the association between the respiratory rate–oxygenation (ROX) index and the National Early Warning Score 2 (NEWS2) score with orotracheal intubation (OTI) and in-hospital mortality in patients with cardiogenic pulmonary oedema (CPE). Methods: This retrospective observational study enrolled patients aged 18 years or older who had developed CPE at admission or during hospital stay. Demographic, clinical, and laboratory data were collected within the first 24 h of CPE onset from the electronic records. The outcomes needed for OTI during 24 h after CPE diagnosis and in-hospital mortality were also collected. The ROX index and NEWS2 were calculated using variables collected at CPE occurrence. Results: Two hundred eighty-six patients with CPE were evaluated; however, 68 patients were excluded due to the absence of variables to calculate the ROX index. Thus, we included 218 patients in the analysis. The mean age was 67.8 ± 14.0 years, 51.8% were female, the median of the ROX index was 9.29 (6.06–13.05), and the median of the NEWS2 was 10.0 (7.0–12.0). Amongst these patients, 28.0% needed OTI 24 h after CPE and 30.3% died. In univariate analysis, lower values of the ROX index and higher values of the NEWS2 were associated with OTI. There was no association with mortality. In logistic regression models, the ROX index and NEWS2 were associated with OTI when adjusted by smoking, time of CPE, and endovenous nitrate and morphine (ROX index: odds ratio [OR] = 0.908, 95% confidence interval [CI] = 0.843–0.979, p = 0.012; NEWS2: OR = 1.261, 95% CI = 1.049–1.514, p = 0.013) and when adjusted by age, sex, and time of CPE (at admission or during hospital stay; ROX index: OR = 0.909, 95% CI = 0.847–0.976, p = 0.008; NEWS2: OR = 1.190, 95% CI = 1.015–1.396, p = 0.032). Conclusions: The ROX index and NEWS2 were associated with OTI in CPE despite no association with mortality.
Keywords: Cardiogenic pulmonary oedema; NEWS2; Orotracheal intubation; ROX index